"Oh" + Apology + Solution: A Practice for Managing the Concomitant Presence of a Possible Offense and a Problem-to-be-Solved. Issue 1 (2nd January 2016) - Pino, Marco; Pozzuoli, Loredana; Riccioni, Ilaria; Castellarin, Valentine
Abstract : In this article we examine a turn construction ("oh"+apology+solution) that speakers use to deal with the concomitant presence of a possible offense and a problem-to-be-solved in the immediately preceding interactional environment. We show that speakers collaborate in differentiating the offense aspect and the problem aspect of an emerging circumstance by treating the apology component as preliminary to and in the service of the primary function of the turn: treating the circumstance as a problem-to-be-solved and providing a solution for it. The "oh" prefacing, which treats the circumstance as something of which the speaker had not been previously aware, and the turn-medial positioning of the apology contribute to treating the matter at hand as a minor shortcoming or imposition rather than a major wrongdoing.